Longitudinal study of factors affecting taste sense decline in old‐old individuals. (4th November 2016) - Ogawa, T.; Uota, M.; Ikebe, K.; Arai, Y.; Kamide, K.; Gondo, Y.; Masui, Y.; Ishizaki, T.; Inomata, C.; Takeshita, H.; Mihara, Y.; Hatta, K.; et al.
Summary: The sense of taste plays a pivotal role for personal assessment of the nutritional value, safety and quality of foods. Although it is commonly recognised that taste sensitivity decreases with age, alterations in that sensitivity over time in an old‐old population have not been previously reported. Furthermore, no known studies utilised comprehensive variables regarding taste changes and related factors for assessments. Here, we report novel findings from a 3‐year longitudinal study model aimed to elucidate taste sensitivity decline and its related factors in old‐old individuals. We utilised 621 subjects aged 79–81 years who participated in the Septuagenarians, Octogenarians, Nonagenarians Investigation with Centenarians Study for baseline assessments performed in 2011 and 2012, and then conducted follow‐up assessments 3 years later in 328 of those. Assessment of general health, an oral examination and determination of taste sensitivity were performed for each. We also evaluated cognitive function using Montreal Cognitive Assessment findings, then excluded from analysis those with a score lower than 20 in order to secure the validity and reliability of the subjects' answers. Contributing variables were selected using univariate analysis, then analysed with multivariate logistic regression analysis. We found that males showed significantly greater declines in taste sensitivity for sweet and sour tastes than females. Additionally, subjects with lower cognitive scores showed a significantly greater taste decrease for salty in multivariate analysis. In conclusion, our longitudinal study revealed that gender and cognitive status are major factors affecting taste sensitivity in geriatric individuals.